Logika Tasawuf Yang Benar - Thulus Gajay Syahbana; Nunu Burhanuddin (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
This research itself is motivated by the many findings in the field regarding Sufism that are not in accordance with what they should be. This could be because Sufism is the highest science and can only be practiced by certain people. So this research itself aims to find out the correct logic of Sufism. So this research itself is deductive in nature, which in the discussion will use the author's logic in expressing the correct logic of Sufism so that there are no more mistakes so that the purity of the concept of Sufism itself can be well maintained. The logical result of the author's own thoughts is that when a person has reached the level called Sufism, his Sufism must be true Sufism, not strange things. Like going to the forest for 40 days and not coming back, that's dangerous and should be done the right way. True Sufism is learning the Shari'a, learning to worship, praying correctly, tahajjud correctly, fasting correctly, reading the Koran correctly, and performing other acts of worship correctly. If all that is true, then later the heart will be clean.